Proses perumusan pancasila dalam sidang BPUPKI 1945 - rohmah, nayla nayla (Maliki Interdisciplinary Journal, 2025)
Pancasila required a long and complex formulation process as the foundation of the Indonesian state, born from the struggle for independence amidst Japanese occupation. It began with the independence promise by Japanese Prime Minister Koiso in 1944, the formation of BPUPKI (Badan Penyelidik Usaha Persiapan Kemerdekaan Indonesia) on April 29, 1945, and two main sessions: the first (May 29–June 1, 1945) focused on the basic principles of the state, and the second (July 10–17, 1945) for drafting the Constitution. Three key figures contributed ideas: Muhammad Yamin with five principles such as Peri Kebangsaan (National Spirit) and Social Justice; Prof. Soepomo who emphasized legal, historical, and integralist aspects of the state; and Soekarno on June 1, 1945, who introduced the term Pancasila, encompassing nationalism, internationalism, deliberation, social welfare, and cultured divinity. Humanity that is Just and Civilized, the Unity of Indonesia, Democracy Guided by the Inner Wisdom in the Deliberation of Representatives, and Social Justice for All the People of Indonesia. Pancasila is not merely an ideology, but also the nation's identity that combines religion, mutual cooperation, and justice in efforts to create a fair, peaceful, and prosperous society amidst the nation's diversity (Bhinneka Tunggal Ika), in accordance with the 1945 Constitution (Articles 29, 33–34). The article emphasizes daily implementation through worship, deliberation, and mutual cooperation, as well as suggestions: interactive Pancasila education in schools, application in families and communities via positive social media, and government policies for equitable welfare. Thus, Pancasila serves as a filter for foreign cultures, prevents fanaticism, and forms the foundation for national progress.